(untitled) (Economic and Political Thought, 2015)
The article raises the issue of transformation in contemporary international trade and its impact on the policy of the European Union. Economic globalisation, global value chains, growing new economic powers threatened the position of the European Union, which had to choose the right strategy for responding to these changes. Free trade has become the ideological determinant of EU policy, which guarantees economic growth in both developed countries and developing countries. The article consists of three parts, introduction and summary. The first part of the article presents the implications of globalisation for modern international trade relations. The second part was devoted to the analysis of the Union’s policy towards the ongoing transformations. In the third presents the methodology used by the Union in the implementation of the idea of free trade.